Microvertebrates of the Lourinhã Formation (Late Jurassic, Portugal) - Guillaume, Alexandre Renaud Daniel (2018)
The Upper Jurassic of Portugal has been globally known for its microfossil vertebrate fauna thanks to the Konzentrat-Lagerstätte of the Guimarota mine, which provided thousands of bone fragments, isolated teeth, and even complete specimens. Other vertebrate microfossil assemblages have been studied around the world. Besides Guimarota, no other Portuguese Jurassic assemblage has been extensively studied. Hereby is presented a revision of the state of the art on Portuguese microvertebrate record, and the first microvertebrate studies on three localities from the Lourinhã Formation (Late Jurassic) hosted by a Portuguese institution; Porto das Barcas, Zimbral, and Valmitão has provided 2,497 microvertebrates skeletal remains and teeth, from which 824 specimens have been identified, described and assessed to the conservative-most taxa. The stratigraphy and sedimentology of the localities suggest that Porto das Barcas and Zimbral were floodplain mud deposits, and Valmitão was an oxbow lake mud deposit, with a slow rate of sedimentation. The remains have been attributed to fishes, amphibians, squamates, crocodylomorphs, and dinosaurs; but unfortunately, no mammaliaform material has been collected. Paleoecological analyses suggest Zimbral and Valmitão were dominated by a terrestrial fauna and more diverse than Porto das Barcas, dominated by an amphibious fauna. The Lourinhã Formation appears to have been closer to the shoreline than American localities in the Morrison and Cloverly Formations were, but more continental than Buenache and Las Hoyas localities (Spain) with swamp to lacustrine paleoenvironments. A detailed study on 125 crocodylomorph teeth from Valmitão support the presence of Goniopholididae, at least two Atoposauridae taxa, and Bernissartiidae in the Late Jurassic of Portugal, with a fauna either dominated by relative small individuals, either juveniles or adults or small taxa.